Rancang Bangun Sistem Informasi Persediaan Dan Penjualan Barang Pada Toko Herik Berbasis Web - Figolius Herik; Kristina; Thommy Willay (INTEKSIS, 2025)
Toko Herik is a business engaged in the sale of daily necessities located in Entikong District, Sanggau Regency, West Kalimantan Province. In its operational activities, Toko Herik still uses manual methods for recording inventory and sales, such as bookkeeping and Microsoft Excel. These methods often lead to various issues, including data recording errors, delays in report generation, and difficulties in monitoring stock in real-time. This study aims to identify the existing problems and design an information system that can assist in managing inventory and sales more effectively and efficiently. The research method used is descriptive, which involves describing and analyzing the current system conditions by collecting data such as product data, sales data, stock data, and supplier data. The analysis of this data is used to design an information system that meets the operational needs of Toko Herik. As a solution, a web-based inventory and sales information system is designed. This system is developed using technologies such as HTML, CSS, JavaScript, PHP, and MySQL, with Bootstrap used to create a responsive user interface. The main features of the system include product data management, sales transaction recording, stock management, and the generation of inventory and sales reports. With the implementation of this information system, Toko Herik is expected to manage its inventory and sales activities more quickly, accurately, and in a more organized manner, thereby increasing operational efficiency and supporting better decision-making.